One-dimensional SnO2 nanostructures : synthesis and applications - Pan, Jun (2013)
Nanoscale semiconducting materials such as quantum dots (0-dimensional) and one-dimensional (1D) structures, like nanowires, nanobelts, and nanotubes, have gained tremendous attention within the past decade. Among the variety of 1D nanostructures, tin oxide (SnO2) semiconducting nanostructures are particularly interesting because of their promising applications in optoelectronic and electronic devices due to both good conductivity and transparence in the visible region. This article provides a comprehensive review of the recent research activities that focus on the rational synthesis and unique applications of 1D SnO2 nanostructures and their optical and electrical properties. We begin with the rational design and synthesis of 1D SnO2 nanostructures, such as nanotubes, nanowires, nanobelts, and some heterogeneous nanostructures, and then highlight a range of applications (e.g., gas sensor, lithium-ion batteries, and nanophotonics) associated with them. Finally, the review is concluded with some perspectives with respect to future research on 1D SnO2 nanostructures.